-8(1-3x)=-7(-4-4x)

Simple and best practice solution for -8(1-3x)=-7(-4-4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(1-3x)=-7(-4-4x) equation:



-8(1-3x)=-7(-4-4x)
We move all terms to the left:
-8(1-3x)-(-7(-4-4x))=0
We add all the numbers together, and all the variables
-8(-3x+1)-(-7(-4x-4))=0
We multiply parentheses
24x-(-7(-4x-4))-8=0
We calculate terms in parentheses: -(-7(-4x-4)), so:
-7(-4x-4)
We multiply parentheses
28x+28
Back to the equation:
-(28x+28)
We get rid of parentheses
24x-28x-28-8=0
We add all the numbers together, and all the variables
-4x-36=0
We move all terms containing x to the left, all other terms to the right
-4x=36
x=36/-4
x=-9

See similar equations:

| .7+.3x=2x-7 | | 12x-13-x=10x | | -7(-4-2n)=-4(8+4n) | | 3x/4+2x72=8/11 | | -3(1-x)-2x=6-4(x-4) | | (z-5)(z^2-10z+25)=0 | | 8x-22/6=7 | | 3n+2(3n-6)=6(n-4) | | k−6.79=6.31 | | 2(-6x-7)+8x=-(x-7) | | 5x-75-3x=180 | | 3x+78=48 | | (2x+1)/37=5 | | 2k=-7.2 | | 2x+9-6x=19 | | -4(k+1)=-2(6k-4)+4 | | 2x+9=x+13 | | (x-3)/5=-22 | | 4(k-5)-8=-8(k-7) | | 5.50h+20=6.50h+15 | | N=3n+16 | | 3(a+8)+1=-3(3-7a)-2 | | 57-3=2y+9 | | 8a+4=6a+4 | | 3(2-k)=-3k=2 | | x/4-19=20 | | -3(6+3x)=-(6x+3) | | 6+8x=11x | | y/5+10=11 | | -3x+10=-38 | | 6(m-4)+5=-5(6-m) | | -2x+8(x+7)=7+5(1-x) |

Equations solver categories